La Fiesta de las Cruses, expresion del sincretismo cristiano - indigena - Ramirez Bautista, Bernardino (2009)
In the present article examines the long and difficult process that followed the Spaniards to evangelize and indoctrinate the Andean population from the moment of conquest, with crosses, saints, virgins and the Christ. Moreover, the Indians together in villages reduction, conducting meetings for the Conciliar repression manifested in the extirpation of idolatries. The natural resistance that people from their enslavement to their tutelary gods, their Pacarinas, huacas and their priests or priestesses. Imposition by the Spanish cultural events took place that gradually accepted by the Catholic Church, as a habit of leaving the Andean peoples. One of these was the great popular festival in Huamantanga, Canta, known as the Feast of the Cross held on January 6 of each year. This feast is linked to the farming communities and linked to the agricultural calendar of the people of the Peruvian countryside. Corresponds to the beginning of the rains, the sowings, of the thunder, the lightning and the hail. Locals consider the holidays as a Catholic origin. This was causing the religious syncretism in Peru.